Health Systems Factors influencing Initiation to Human papillomavirus Vaccination among Adolescent Girls aged 9 to 17 years in Eastern Uganda. A Cross-sectional Study. - Wangwa, Fred (Student's Journal of Health Research Africa, 2022)
Background In many parts of Africa, cervical cancers are not identified or treated until advanced stages due to insufficient access to reproductive health care services, effective screening, and early treatment. To reduce the cervical cancer burden in the African Region, WHO will continue to support Ministries of Health to implement priority cancer prevention and control interventions that cut across the continuum of prevention, early detection, diagnosis, treatment, and palliative care services. The objective of the study is to determine Health systems factors influencing the initiation of Human papillomavirus Vaccination among adolescent girls aged 9 to 17 years in Eastern Uganda. Methodology: The study adopted a population-based cross-sectional study design in which questionnaires were used to collect data. The data were analyzed in STATA. Data was collected from 4th/01/2021 to 20th/05/2022. Results: Health systems factors influencing initiation of HPV vaccination include perceived knowledgeability of health workers about HPV vaccines by the caretakers, community sensitization about HPV vaccination, availability of vaccines at the health facilities, and quality of care offered at the health facility. These are all reported with p-values less than 0.05 when assessed at bivariate Conclusion: Health systems characteristics play a role in influencing caretakers towards initiation to HPV vaccination when assessed in isolation. These factors significantly influence the caretaker’s decision to initiate their adolescent girls to HPV vaccination. Recommendations: The District Health Officer should as a practice organize community sensitization about HPV vaccination for adolescent girls. This further calls for resource mobilization, since key informants who were in charge of health facilities reported inadequate funding) to ensure proper facilitation of medical staff from the district to lower health center levels.